2019
DOI: 10.3390/jcm8101688
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulin Levels in Children with Sickle Cell Disease: A Large Prospective Study

Abstract: Over the past 3 decades, the pediatric department of the university Intercommunal Créteil hospital, a referral center for sickle cell disease (SCD), has prospectively evaluated immunoglobulin (Ig) levels in a cohort of 888 children with SCD, including 731 with severe sickle genotypes (HbSS and HbSβ0 thalassemia) and 157 with milder genotypes (HbSC and HbSβ+ thalassemia). We found consistent sickle genotype differences in levels of IgG and IgA, with increased levels of IgA and IgG in the severe versus milder ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…As regards serum immunoglobulins, our data are partially supported by the literature, as in the SCD HU− subgroup, IgG significantly expanded when compared to individuals with a base health condition; the same goes for IgA, although this finding did not reach statistical significance, probably as a consequence of the low sample size [ 30 ]. Moreover, IgM decline in the SCD HU− subgroup, albeit not reaching statistical significance, was potentially due to functional hypo-/a-splenism-related deficiency of antibody-producing (switched) memory B-cell subsets, corresponding to what has been recently observed by Cherif-Alami et al, although discordant findings emerged from previous studies in the literature [ 7 , 18 , 30 , 31 , 32 ]. Our results could be explained by the above-mentioned compensatory output of IFN-γ-producing memory NK cells, directly activating B-cell production of IgG and promoting IgM class switching to IgG and IgA [ 31 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…As regards serum immunoglobulins, our data are partially supported by the literature, as in the SCD HU− subgroup, IgG significantly expanded when compared to individuals with a base health condition; the same goes for IgA, although this finding did not reach statistical significance, probably as a consequence of the low sample size [ 30 ]. Moreover, IgM decline in the SCD HU− subgroup, albeit not reaching statistical significance, was potentially due to functional hypo-/a-splenism-related deficiency of antibody-producing (switched) memory B-cell subsets, corresponding to what has been recently observed by Cherif-Alami et al, although discordant findings emerged from previous studies in the literature [ 7 , 18 , 30 , 31 , 32 ]. Our results could be explained by the above-mentioned compensatory output of IFN-γ-producing memory NK cells, directly activating B-cell production of IgG and promoting IgM class switching to IgG and IgA [ 31 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our finding that IgM concentration did not differ between patients of different genotypes or controls aligns with previously published data 30,31 . A study which assessed splenic function by radionucleotide scan found that enlarged spleens correlated with IgM elevation, but normal or small spleens were associated with normal IgM concentrations in the serum 32 .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that IgM concentration did not differ between patients of different genotypes or controls aligns with previously published data. 30,31 A study which assessed splenic function by radionucleotide scan found that enlarged spleens correlated with IgM elevation, but normal or small spleens were associated with normal IgM concentrations in the serum. 32 However, in this study also, the correlation between spleen size and IgM in children with HbSC disease was stronger than the relationship between spleen size and HbSS disease.…”
Section: Complications Of Scd Are Not Associated With Umbc Frequencymentioning
confidence: 99%
“…Nonetheless, glutamine is also known for its anti-inflammatory roles, since it suppresses the NFκB and STAT pro-inflammatory pathways [24]; therefore, in a disease characterized by a steady inflammatory state, like SCD, its administration could be beneficial in terms of inflammatory phenotypes. Indeed, our results support a slightly differentiated inflammation profile when glutamine is present in higher doses, as evidenced by the lower levels of lymphocytes, and immunoglobulins, which might both be increased in the specific disease setting [25,26], as well as the decreased levels of inflammation markers like ferritin.…”
Section: Higher Dose Of L-glutamine Is Protective In Terms Of Oxidati...supporting
confidence: 76%